2016
DOI: 10.1136/bjsports-2015-095648
|View full text |Cite
|
Sign up to set email alerts
|

Total sitting time and the risk of incident diabetes in Danish adults (the DANHES cohort) over 5 years: a prospective study

Abstract: The association between total sitting time and incident diabetes is substantially moderated by physical activity and obesity. Total sitting time remains a risk factor for diabetes only in inactive and obese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 30 publications
5
42
0
1
Order By: Relevance
“…The Danish cohort study suggested that sedentary time is associated with increased diabetes risk among inactive or obese people [6]. Our results are also consistent with those of meta-analyses of sedentary time and all-cause mortality, which indicate that prolonged sitting may have adverse effects particularly among inactive people [2,13].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The Danish cohort study suggested that sedentary time is associated with increased diabetes risk among inactive or obese people [6]. Our results are also consistent with those of meta-analyses of sedentary time and all-cause mortality, which indicate that prolonged sitting may have adverse effects particularly among inactive people [2,13].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our results, television time was more strongly than other types of sitting associated with type 2 diabetes incidence in a 6 year follow-up of the Nurses' Health Study [4]. Also, a Danish cohort study observed a moderate 35% risk increase of any diabetes associated with total sitting ≥10 h/day compared with <6 h/day, but the association was largely attenuated after adjustment for physical activity and BMI [6].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Such a breadth of confounding has not been fully accounted for by studies in the field. Beyond TV time, a recent study of total sitting and incident diabetes in a sample of adults from Denmark found associations only among the physically inactive and the obese groups 19. Sitting can occur in many different contexts (eg, work, leisure time and transportation), and there is a limited number of cohort studies9 20 21 that examined context-specific associations with diabetes risk (all US-based).…”
Section: Introductionmentioning
confidence: 99%
“…По мнению авторов, ассоциация между общим временем сидя и частотой новых случаев СД2 су-щественно опосредуется ФА и ожирением. Общее время сидения остается фактором риска СД2 только в неактив-ных популяциях и при ожирении [28].…”
Section: сахарный диабет Diabetes Mellitusunclassified